OTUB1 Recruits Tumor Infiltrating Lymphocytes and Is a Prognostic Marker in Digestive Cancers - Zhang, Wenhao; Qiu, Wenlong (Frontiers in Molecular Biosciences, 2020)
Background: OTUB1 is a de-ubiquitinating enzyme (DUB) that can regulate the process of ubiquitination. The further exploration of OTUB1 in the prognosis of digestive cancers and tumor-infiltrating lymphocytes (TILs) is important for the design of new drug targets. Methods: We analyzed the expression of OTUB1 with Oncomine and TIMER database. The association between OTUB1 and clinical prognosis was calculated with Kaplan-Meier plotter. We investigated the correlations between OTUB1 and cancer immune infiltrates, and the correlation between copy number variation (CNV) of OUB1 and TILs with TIMER. We analyzed the correlations between OTUB1 and immune genes, gene expression profiling (GEP), key genes of apoptosis and autophagy via GEPIA. Protein-protein interaction (PPI) and gene expression profiling (GEP) analysis were analyzed with STRING and Pathway Common database specifically. Functional pathway enrichment analysis was conducted with Pathway database. Results: High OTUB1 expression was found in CHOL, LIHC, READ, ESCA and COAD. This high expression was significantly associated with poorer OS of LIHC (HR = 2.07, 95% CI = 1.30-3.30, P = 0.002). Specifically, high OTUB1 expression was correlated with worse OS in stage 1, stage3, and grade2, grade3, male, Asian, and patients with a high mutant burden. The expression of OTUB1 has significant correlations with B cells, CD8+ T cells, macrophages infiltration level in ESCA, and B cells, neutrophils in LIHC. The CNV of OTUB1 also exerted influence infiltration level of tumor-infiltrating lymphocytes in researched cancers. OTUB1-centered protein-protein interaction (PPI) enrichment was constructed with the STRING database. The 10 most significant genes showing significant interaction were USP8, RNF128, LRIG1, UBB, UBC, STAM2, RNF41, EGFR, RPS27A and HGS. The functional pathway enrichment analysis showed that OTUB1 also can regulate the process of immune, apoptosis, and autophagy through TP53 and ATG. Conclusions: OTUB1 is associated with the prognosis of specific digestive cancers, and modifies tumor lymphocyte infiltration, including CD8+ T cells, CD4+ T cells, macrophages, neutrophils, and DCs. OTUB1 participates in ubiquitination, immunity, apoptosis and autophagy, and is a potent novel antitumor target for digestive tumors.